Xinjang, China. Silk Road Fashion - Wagner, Mayke (e-Forschungsberichte des DAI, 2023)
Under the title “Silk Road Fashion: Clothes as a means of communication in the 1st millennium BC, Eastern Central Asia”, a joint German-Chinese group of researchers are investigating garments excavated from modern Xinjiang, Uyghur Autonomous Region of Western China. Various disciplines are working together within contemporary state of knowledge concerning the quality of the material, means of processing and the use of resources. The practical intent of the documentation and research results lies in the development of sustainable techniques enabling the physical preservation of cultural relics in Xinjiang and its virtual accessibility worldwide. The Chinese Academy of Cultural Heritage is responsible for organizing the education and training of restorers involved in the search for and conservation of all material in China.